PKM meningkatkan kemampuan mengajar guru dengan pendekatan saintifik berbantuan perangkat lunak Geogebra - Asdar Asdar; Rosidah Rosidah; Fajar Arwadi (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
The aim of this activity was to increase the pedagogic competence as well as the professional competence of teachers in the form of Community Partnership Program (PKM). The community involved in this study was a group of mathematics teachers in Tinggi Moncong subdistrict, one of subdistricts in Gowa, South Sulawesi Province, Indonesia. It was undertaken to solve the problem, i.e., the lack of integration of pedagogic competence, subject matter knowledge, and technological skill to apply in classroom. In addition, the other problem behind this program was no instructor who could facilitate them in such competence enhancement. This program trained the teacher to use geogebra. The findings of this program were that the professional competence and pedagogical competence of teachers increased.